Mathematical modeling of options for osteosynthesis of middle third clavicle fractures - Karpinsky, Mykhaylo; Yaresko, Oleksandr; Pavlenko, Konstantin; Topor, Volodymyr; Uvarova, Olena; Popov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Fore consolidation of the clavicle fragments and restoration of function in damaged extremity it is necessary to create optimum conditions including an accurate comparison of bone fragments, their reliable fixation, following the rules of asepsis, preservation of blood circulation, active management in the postoperative period. We propose to use this lock original design. Purpose: mathematical model to conduct a comparative analysis of the stress-strain state (SSS) system «collarbone – implant» fracture in the middle third of the clavicle in a different osteosynthesis holders. Methods: mathematical models clavicle fracture with the middle third. Simulated three options osteosynthesis: extramedullary plate, intramedullary nail, the original design of the machine. VAT study models performed using the finite element method. In the first stage studied VAT system «collarbone – implant» under the influence of compressive loads, the second — bending, the third — twisting. Results: It was found that the most dangerous loads are bending. Stresses in the clavicle bone in flexion, may exceed the limit of its strength and cause fractures. Extramedullary plate works well only when the bending loads acting perpendicular to its plane. But if they are parallel to the plane of the plate, the entire burden falls on the extreme screws, and critical to the strength of the bone stresses occur is around them. Intramedullary rod is equally effective when bending loads that act in both vertical and horizontal planes. However, the stresses in the bone cell models are too high. Advantage copyright apparatus is that it keeps the load bending in any direction and prevents overloading the bone.